MICROSTRUCTURE OF STOMATOLOGICAL MATERIAL "RESTAVRIN" BEFORE AND AFTER BACTERIAL COLONIZATION IN THE EXPERIMENT - V. I. Kolodkina; A. A. Arutyunov; A. A. Ovsyannikova; S. A. Babichev (Кубанский научный медицинский вестник, 2018)
Aim. This research was conducted to study the electron microscopic microstructure of the surface of the filling material «Restavrin» coated with the «Easy Glaze» sealant and without it before and after bacterial adhesion by scanning electron microscopy.Materials and methods. There was studied the microrelief of the plates preliminarily made from a polymeric nano-hybrid filling material («Restavrin», Technodent, Russia) with and without the sealant «Easy Glaze» and without it both in the initial state and after being placed in a medium with microorganisms. The material for microbiological examination (the contents of the gingival sulcus) was taken from 23 patients with a diagnosis of «dentine caries» by sterile turundas. The test material was directly placed near the patient's chair in a Petri dish with enriched blood agar. Nutrient media with inoculations were delivered to the laboratory for further research. After selecting the necessary area for scanning at the same magnification (×200) (the size of the scanned section is 50x68 μm2) at a certain vertical interval, 6-8 horizontal lines for scanning were selected.Results. Scanning electron microscopy at the end of the 45-day experiment showed that used S.oralis and S.mutans strains (strains isolated from dental patients’ contents of the gingival joint) have a pronounced ability to adhere what indirectly confirms the formation of glucans by them and, accordingly, their cariogenicity. The destructive effect of oral streptococci (S.mutans + S.oralis) on the surface of the filling materials «Restavrin» and «Restavrin» + sealant «Easy Glaze» was experimentally confirmed that clearly manifests itself after 45 days of joining streptococci and filling materials. It should be noted that the restorative material «Restavrin» under the sealant «Easy Glaze» remained nearly intact during the 45-day in vitro experiment.Conclusion. We consider it advisable to recommend the compulsory covering of the restoration with a sealant because it serves as a kind of barrier protecting the filling material from the effect of oral streptococci. Accordingly, this procedure extends the life of the filling and also ensures the preservation of the aesthetic and mechanical properties of the composite restorations.